Detektor på skördare för utsortering av träd med metallskrot - Lindström, Stefan (2010)
Fortifikationsverket which is the landlord for the Swedish national defence has a great problem in their forestry due to the relatively large amount of metal objects in their timber. These metal objects cause different types of economical losses in the timber refinement chain. To enable out sorting of logs containing metal objects already in the harvesting phase, Fortifikationsverket is interested of the possibility to utilize some type of metal detector in a harvesting head for that purpose.